Whole Process Management-Discussion on Economic Risk Management of General Contract Project - Wang, Qianping (Journal of Theory and Practice of Management Science, 2023)
This paper mainly takes the economic management analysis of the general contract project as the ft starting point, and puts forward specific risk prevention measures according to the risks and related problems in each stage, in order to provide some references and suggestions for improving the level of engineering economic risk management. The software and information technology service industry is a basic, strategic and leading industry that has a bearing on the overall development of the national economy and society. It is characterized by rapid technological renewal, high added value of products, wide application fields, strong penetration capacity, low consumption of resources and full utilization of human resources. It plays an important supporting and leading role in the development of the national economy and society. From 2012 to 2021, the revenue of China's software and information technology service industry increased from 2.5 trillion yuan to 9.5 trillion yuan, with an average annual growth rate of 16%, which is among the highest among all industries in the national economy. Total profits in 2021 reached 1.2 trillion yuan, double that of 2015. In 2022, the GDP of information transmission, software and information technology services grew by 9.1 percent year-on-year.